New Generation Corporate Financial Statements: A Model for Old Format’s Conversion and Comparative Value Analysis - Gupta, Ambrish (Indian Journal of Finance, 2013)
This paper attempts to identify the far reaching revolutionary changes brought about in the reporting of corporate financial statements and the requirements of more comprehensive disclosure of information on the face of the Balance Sheet and the Statement of Profit and Loss itself with effect from 2011-12 reporting. The paper offers a model framework for converting and restating the old schedule VI format financial statements of a company into new-generation schedule VI format, through the case of Reliance Industries Ltd., with a view to provide help and guidance to analysts, academicians and researchers in carrying out a historical comparative study thereof involving both the periods, the period prior to March 31, 2011 and the period from March 31, 2012 onwards. A comparative analysis of the two formats has also been attempted, which reveals that the new format statements enable portrayal of real financial position/revenue/equity holders’ funds, actual liquidity and solvency position, checks the rampant practice of window dressing of the top line, leads to disclosure of net worth straight on the face of the balance sheet, and ultimately, redefines the performance and financial position of a company.